The reporting of methods for reducing and detecting bias: an example from the WHO Misoprostol Third Stage of Labour equivalence randomised controlled trial - Piaggio, Gilda (BioMed Central, 2003)
BACKGROUND: The aim of this article is to explore ways in which selection bias and ascertainment bias can be reduced and investigated in trials, by using the example of a drug trial carried out in both developed and developing countries in hospital delivery wards. METHODS: We describe an innovative and practical design for the boxes for packing the drugs as a way of increasing the security of allocation concealment and blinding. We also assess ascertainment bias using sensitivity analyses, as some unblinding could have occurred due to a potential side effect of one of the drugs. RESULTS: The sensitivity analyses indicated that the conclusions about the relative effects of the treatments could be maintained even in the unlikely worst-case scenarios. CONCLUSIONS: Detailed description of the procedures protecting against common biases and of the assessment of ascertainment bias in this trial should allow readers to confidently appraise and interpret the results obtained. In addition, our experiences will assist others in planning trials in the future.